2017
DOI: 10.1007/s10461-017-1979-z
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Racism and Heterosexism in Medical Students’ Clinical Decision-Making Related to HIV Pre-Exposure Prophylaxis (PrEP): Implications for PrEP Education

Abstract: Social biases among healthcare providers could limit PrEP access. In this survey study of 115 US medical students, we examined associations between biases (racism and heterosexism) and PrEP clinical decision-making and explored prior PrEP education as a potential buffer. After viewing a vignette about a PrEP-seeking MSM patient, participants reported anticipated patient behavior (condomless sex, extra-relational sex, and adherence), intention to prescribe PrEP to the patient, biases, and background characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 49 publications
(72 reference statements)
2
56
3
1
Order By: Relevance
“…Additionally, graduate medical courses should work to debunk racial and other stereotypes about risk compensation, as such biases impede provider willingness to prescribe PrEP (23)(24)(25)34). Future work could examine the extent to which hands-on experiences with high-risk populations (e.g., via clinical rotations) impact both willingness to prescribe and refer.…”
Section: Interdisciplinary Approaches To Prep Carementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, graduate medical courses should work to debunk racial and other stereotypes about risk compensation, as such biases impede provider willingness to prescribe PrEP (23)(24)(25)34). Future work could examine the extent to which hands-on experiences with high-risk populations (e.g., via clinical rotations) impact both willingness to prescribe and refer.…”
Section: Interdisciplinary Approaches To Prep Carementioning
confidence: 99%
“…The few studies were limited to medical students (23)(24)(25)(26) and did not include other health professional students who may play an active role in PrEP care, such as those in nurse practitioner, or pharmacy training programs. Calabrese and colleagues surveyed medical students regarding the influence of patient race (23), sexual orientation (24), and sexual behavior (25) on clinical decision-making related to PrEP. Results demonstrate that medical students' awareness of PrEP was generally high (85%), with half reporting PrEP education during medical school.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they need to address stigma associated with HIV/AIDS and MSM as major factors in the training of future health professionals. This stigma related training should not be supplemental to their usual curricula, but rather as a central aspect of physician/patient interaction training which is required of medical schools (Calabrese et al, 2018;Varas-Díaz et al, 2017). The ongoing HIV/AIDS epidemic among MSM, and the concerns over stigma manifestations during clinical interactions, highlight the importance of medical schools as important scenarios for stigma reduction training.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, researchers found that implicit racist and homophobic biases among health care providers may limit access to PrEP among those patients most in need. A study among medical students found that a prevention paradox in their lack of willingness to prescribe PrEP was inconsistent with patient risk and may have been impacted by implicit racial bias (171). Using data from the Urban Men's Health Study, another study found that the combination that racism and minority sexual orientation status has impacts on Black MSM's encountered everyday racism, and thus Black MSM have a less positive experience with the gay community than their White counterparts (172).…”
Section: Homophobia and Racism: Being A Black Gay Or Bisexual Manmentioning
confidence: 99%